2020
DOI: 10.1097/md.0000000000019577
|View full text |Cite
|
Sign up to set email alerts
|

Over expression of CDK4 and MDM2 in a patient with recurrent ALK-negative mediastinal inflammatory myofibroblastic tumor

Abstract: Rationale: The diagnosis of anaplastic lymphoma kinase (ALK)-negative inflammatory myofibroblastic tumors (IMT) remains challenging because of their morphological resemblance with spindle cell sarcoma with myofibroblastic characteristics. Patient concerns: A 69-year-old female patient presented with loco-regional recurrent IMT several times within 8 years after primary treatment and neck lymph node metastasis 3.5 years after last recurrence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Some researchers have found the existence of cancer stem cells in PIMT tissues ( 24 ), and some studies have reported that the lymph nodes removed during surgery in patients with PIMT were positive ( 23 ). In addition, cervical lymph node metastasis has occurred 3.5 years post-operation ( 25 ). Moreover, the WHO points out that IMT is a borderline tumor with the potential for recurrence and rare metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have found the existence of cancer stem cells in PIMT tissues ( 24 ), and some studies have reported that the lymph nodes removed during surgery in patients with PIMT were positive ( 23 ). In addition, cervical lymph node metastasis has occurred 3.5 years post-operation ( 25 ). Moreover, the WHO points out that IMT is a borderline tumor with the potential for recurrence and rare metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…( 23 ). Some patients with IMT who have tumor tissue removed still experience relapse and distant metastasis ( 25 27 ). In one study, researchers followed up 23 patients after PIMT excision for 2–127 months; in those cases, recurrence only occurred twice after operation, and there was no recurrence after reoperation ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed high-risk clinicopathologic features in uterine IMTs include older patient age, larger tumor size, infiltrative borders, predominance of myxoid morphology, severe cytologic atypia, necrosis, and increased mitotic activity 6,7,29. Proposed IHC and molecular high-risk features from prior studies including IMTs from other anatomic sites have included ALK-negativity, RANPB2::ALK gene fusions in the so-called epithelioid inflammatory myofibroblastic sarcoma, p53 expression, and MDM2 overexpression/amplification 28–35. There is currently a gap in the literature regarding whether molecular alterations drive clinical behavior, perhaps due to the narrow focus on gene fusions that drive IMTs.…”
mentioning
confidence: 99%
“…6,7,29 Proposed IHC and molecular high-risk features from prior studies including IMTs from other anatomic sites have included ALK-negativity, RANPB2::ALK gene fusions in the so-called epithelioid inflammatory myofibroblastic sarcoma, p53 expression, and MDM2 overexpression/amplification. [28][29][30][31][32][33][34][35] There is currently a gap in the literature regarding whether molecular alterations drive clinical behavior, perhaps due to the narrow focus on gene fusions that drive IMTs. To our knowledge, no comprehensive molecular characterization of aggressive IMTs from any site has been reported in the literature.…”
mentioning
confidence: 99%